(3GdHgLI aj TQM GdJMaIs - (3Ydj Hf YHO GdSdGe Hf Ydj, CHh GdMSf GdoqJoShdj, J (B1258(3g`s; (3GHf YGUe , CHh jMji eMeO Hf eMeO Hf eMeO Hf YGUe GdbjSj GdZQfGWj,J (B857 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3JQGLe GdLRA GdChd HGH GdbVGA heG jJYdb Hg ef GdJMcje aUd ai CQcGf GdbVGA aUd ai QaY GdeOYi Ydjg aUd ai eSGFd ef GdbVGA s
(3BNQgG (B:s
(3bdJ hgh XGgQ aEf CKHJJ GdhVjYI hef eYgG VQQge HTgGOI ef Scf eYge RLQ G dXGde HGdSLf hGdVQH hdG JYRd hGMOI efgf Yf GdCgd dCf ZGdH GdfSGA ai gPG GdReGf hGfXQ eG eQ ai VQQ GdRhLjf hGddg CYde GfJgi GdLRA GdChd ef GdJShdi s
(3HgG fXGe GdJYbjHIs
(3YdjgG JUhjHGJ hgj ebQDIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B293 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B199s
Keywords: (3Gdabg GdESdGejs